Manufacturing processes - Laleman, Joseph P.; Preiss, Richard (Manufacturing technology)
Processing takes materials and turns them into finished products. It includes casting, molding, forming, separating, conditioning, assembling, and finishing. Each area is examined and explained. A brief discussion is also given of the properties of manufacturing materials (mechanical, physical, thermal, chemical, electrical, optical, and acoustical).